The Effects of Dietary Olive Cake Meal on Fattening Performance, Carcass and Slaughter Traits in Japanese Quails (Coturnix coturnix japonica) - Cahit Özcan; Tülay Çimrin; Yasin Yakar; Sema Alaşahan (Turkish Journal of Agriculture: Food Science and Technology)
This study was aimed at investigating the effects of dietary supplementation with different levels of olive cake meal (0%, 2.5%, 5% and 7.5%) on the fattening performance and slaughter and carcass traits of quails. For this purpose, 400 one-day-old Japanese quail chicks were randomly assigned to 4 groups, each with 5 replicates. The quails were fed on either a basal diet alone (Control Group) or a basal diet supplemented with olive cake meal at rates of 2.5% (Group I), 5% (Group II) and 7.5% (Group III) for a period of 42 days. At the end of the fattening period, dietary olive cake meal was observed not to have caused any adverse effect on body weight, feed intake and feed conversion rate. Eviscerated hot carcass weight, eviscerated cold carcass weight, wing weight, breast weight, thigh weight and edible visceral organ weights were determined to have improved in the treatment groups that received dietary olive cake meal, when compared to the control group. In conclusion, dietary supplementation with olive cake meal, a waste product of the olive oil industry, at a level of 5%, was observed to produce the closest and most similar results to those of feeding on the basal diet. Thus, it is suggested that olive cake meal could be used as an alternative feedstuff for poultry. Furthermore, the use of olive cake meal as an alternative feedstuff would contribute to reducing both feed costs and environmental pollution.